HISTOLOGI HATI MENCIT (Mus musculus L.) YANG DIBERI EKSTRAK DAUN LAMTORO (Leucaena leucocephala) - Andi Yoga Kurniawan, I Wayan; Intan Wiratmini, Ngurah; Sudatri, Ni Wayan (SIMBIOSIS; Vol 2 No 2 (2014))
Leucaena (Leucaena leucocephala) has been used as traditional medicine, such as drugs to decrease the level of blood glucose, so it can be used as drug to indicate diabetes. The aim of this research is to study the histopathological change of mice’s liver given leucaena leaf extract. This research used 24 male mice that were divided into 4 groups by completely randomized design. Group P0 (control) were given 0,9 % NaCl, and groups P1, P2, and P3 were given 0,5 g / kg bw, 1 g / kg bw, and 1,5 g / kg bw leucaena’s leaf extract by oral administration respectively. The treatment were given daily for 30 days. All of the mice were necropsied at day 31, and the liver were taken to examine their histopathological change. Histopathological change examination were based on the present hydropic degeneration, fatty degeneration, and apoptosis surround central vein. Result of statistically analised by ANOVA and Kruskal-Wallis method indicated no significance difference among the control and treatments. There was no significance toxicity effect of leucaena leaf extract of all treatment dosage on mice liver. Keywords: Leucaena leucocephala, liver histology, Mus musculus L.